The Nutritive Value of Cocoa Shell in Ruminants - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: The nutritive value of cocoa shell was studied by in vitro and nylon bag technique and a feeding trial was also carried out in growing cattle. Cocoa shell contains 17.6% CP, 4.6% fat, 46.6% NDF,0.36% Ca, 0.61% P, 0.06% Na, U 61% Mg and 1.6 % theohromine. The dry matter (DM) digestibility of cocoa shell was 63.5 % and within 48 lir 50 % of the DM disappeared from the rinucri. Approximately 30 % of cocoa shell protein disappeared from the rumen after l 2 h and there was .small increase after that time. Whereas for fat, there was an increasing amount disappeared from the amen after l 2 hr but may reach the maximum value (73 %) at 48 hr. Cocoa shell is a good source of energy and minerals, P and Mg for ruminants Five levels of cocoa shell (CS), 7. 17, 27, 37 and 47 'A, were included in the concentrate to study (I) theobromine disappearance in the rumen, (II) its effect on growing cattle_ In experiment 1. 2 fistulated Ougole fed elephant grass ad libitum plus 2 kg concentrate (with 7 % CS) were used to suspend the nylon bag containing different levels of CS. Almost all of theobromme disappeared from nylon bag at 24 lir incubation. aild there was no difference with 48 hr incubation In experiment II, thirty Ongolc (144 + 12.2 kg) were randorolv divided into 5 treatment groups recieving elephant grass ad libitum concentrate (1.2% Live Weight) containing different levels of CS . The experiment lasted for go days. There were no differences in intake of dry matter (CM) and metabohsablc enery (ME) between the treatments. Live weight gain was not affected by feeding less than 27 CS in the concentrate (or 1 1% in the ration). However, at 37% CS (or 15 % the ration), live weight gain staileti to decline At fins level the ration contains approximately 0.24 lYa theobronune which may be responsible for reduced utilisation of metabolisable energy.